2019
DOI: 10.1210/clinem/dgz004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Resting State Connectivity Responses to Glycemic State in Type 1 Diabetes

Abstract: Context Individuals with type 1 diabetes mellitus (T1DM) have alterations in brain activity that have been postulated to contribute to the adverse neurocognitive consequences of T1DM; however, the impact of T1DM and hypoglycemic unawareness on the brain’s resting state activity remains unclear. Objective To determine whether individuals with T1DM and hypoglycemia unawareness (T1DM-Unaware) had changes in the brain resting sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A recent study has shown important differences in the DMN connectivity response in people with diabetes and normal awareness of hypoglycaemia that is lost in impaired awareness. 34 The DMN has been widely studied and is known to be disrupted in numerous disease states. 35 The impact of awareness status on the effect of hypoglycaemia induction in resting state networks, other than the DMN, has not been explored in previous connectivity studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown important differences in the DMN connectivity response in people with diabetes and normal awareness of hypoglycaemia that is lost in impaired awareness. 34 The DMN has been widely studied and is known to be disrupted in numerous disease states. 35 The impact of awareness status on the effect of hypoglycaemia induction in resting state networks, other than the DMN, has not been explored in previous connectivity studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study does have some limitations. Previous resting state analyses have had, at most, 12 participants with IAH 34 and this is the largest resting state functional neuroimaging study investigating hypoglycaemia in diabetes of which we are aware. Despite this, we may have lacked power and missed important changes in brain connectivity due to hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis by Nicolas et al ( 22) has examined the alterations of RSNs during the induction of hypoglycemia in diabetic and control subjects, and found changes in multiple RSNs, such as DMN, SMN, play an important role in awareness and behavioral response to hypoglycemia. Parikh et al (23) also found the decreased connectivity in angular gyrus within DMN was correlated with greater symptoms of hypoglycemia as well as higher scores of perceived stresses. Alterations in brain network responses to hypoglycemia are increasingly described, and the brain regions and networks that are sensitive to variations in plasma glucose levels have been identified (24).…”
Section: Introductionmentioning
confidence: 92%
“…Parikh et al. ( 23 ) also found the decreased connectivity in angular gyrus within DMN was correlated with greater symptoms of hypoglycemia as well as higher scores of perceived stresses. Alterations in brain network responses to hypoglycemia are increasingly described, and the brain regions and networks that are sensitive to variations in plasma glucose levels have been identified ( 24 ).…”
Section: Introductionmentioning
confidence: 93%
“…We used the novel fMRI technique, intrinsic connectivity distribution (ICD), to measure synchronous brain activity during a visual task, identifying patterns of correlated neural activity and providing insights into how brain regions interact with each other in response to different conditions [22,23]. ICD uses a whole-brain voxel-wise approach that does not require a prior selection of predefined brain regions (seed-based) [22,24] to determine brain connectivity and can be performed across different types of tasks [23,25]. The absence of seed region selection ensures a data-driven approach, allowing the identification of connectivity patterns that may not have been considered in advance.…”
Section: Introductionmentioning
confidence: 99%